Rimonabant potentiates the antifungal activity of amphotericin B by increasing cellular oxidative stress and cell membrane permeability. Issue 3 (11th March 2021) - Zhang, Ming; Lu, Jinghui; Duan, Ximeng; Chen, Jinyao; Jin, Xueyang; Lin, Zhaomin; Pang, Yingxin; Wang, Xuexiang; Lou, Hongxiang; Chang, Wenqiang
ABSTRACT: Amphotericin B (AmB) is a very effective antifungal agent, and resistance in clinical isolates is rare. However, clinical treatment with AmB is often associated with severe side effects. Reducing the administration dose of AmB by combining it with other agents is a promising strategy to minimize this toxicity. In this study, we screened a small compound library and observed that the anti-obesity drug rimonabant exhibited synergistic antifungal action with AmB against Candida species and Cryptococcus neoformans . Moreover, the combination of AmB and rimonabant exhibited synergistic or additive effects against Candida albicans biofilm formation and cell viability in preformed biofilms. The effects of this combination were further confirmed in vivo using a murine systemic infection model. Exploration of the mechanism of synergy revealed that rimonabant enhances the fungicidal activity of AmB by increasing cellular oxidative stress and cell membrane permeability. These findings provide a foundation for the possible development of AmB–rimonabant polytherapies for fungal infections. Abstract : The combination of amphotericin B and rimonabant exhibits synergistic activity against fungal pathogens, including planktonic cells and biofilms, through increasing cellular oxidative stress and cell membrane permeability.